“Como uma flor agreste”: ferrovias, campo e cidade no interior da Bahia (1923 – 1937) - Almeida, Lucas Adriel Silva de (2014)
The focus of the investigation for this research line is the formation of Mundo Novo region in Bahia state between 1923 until 1937. In this context, we analyze daily this space highlights local elite strategies to create the appropriate environment for the main tenance in farm activities, their relation with the construction about three stations of train and ideal about civility inspired by the great urban centers through in Brazil. This work consist in notice the tactic perceived by the mainly habitants and the way to consumption dominant perimeter, thus showing dissenting practice to our propose. Finally, it problematizes the dialog between countryside and city amid developed through walkers. In order to achieve the research's main goal, we have various source: newspaper that circulated in city, municipal legislative, manuscripts, memorandum, photographers, railway undertaking report and governor of the state’s message.